2012
DOI: 10.5120/8166-1406
|View full text |Cite
|
Sign up to set email alerts
|

An Economic Model of the Consumers' Online Shopping Utility and Factors Affecting on Online Shopping

Abstract: This paper integrates extant literature on retailing and consumer choice to develop an economic model of consumer choice in which a consumer self-selects on-line shopping. Three important factors impacting consumer choice of on-line shopping: (1) the online shopping utility (2) the consumers' perceived product and service risks (Perceived Privacy Protection, Perceived Security Protection etc.) and (3) consumer and e-vendors qualities (Consumer Disposition to trust, E-vendors' Positive Reputation etc.) . Our mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The sense of virtual community has significant effect on OGB intention was found by Cheng et al (2012) as well. In addition, Azam and Qiang (2012) found that familiarity with other purchasers in the same sites has strong influence on OGB. However, in the case of OGB, we have not observed that virtual community matters.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The sense of virtual community has significant effect on OGB intention was found by Cheng et al (2012) as well. In addition, Azam and Qiang (2012) found that familiarity with other purchasers in the same sites has strong influence on OGB. However, in the case of OGB, we have not observed that virtual community matters.…”
Section: Discussionmentioning
confidence: 94%
“…Choice for online purchasing is impacted by online shopping utility, customers perceived service risk and customers e-vendors qualities, such as attitude for risk, reputation (Azam & Qiang, 2012). Usefulness and easy to use navigation are primary motives to use the website.…”
Section: Online Group Buying In Leisure Servicesmentioning
confidence: 99%
“…Thus, there are a lot of of advantages of e-commerce for customers. Three important factors, what impact the consumer choice of on-line shopping are as follows: the online shopping utility, the consumers' perceived product and service risks (perceived privacy protection, perceived security protection), consumer and e-vendors qualities (consumer disposition to trust, e-vendors' positive reputation) (Azam and Qiang, 2012). There are also some disadvantages, such as unsecure payment information (the necessity to give credit card number) or shipping costs are too high.…”
Section: E-wom As Toolmentioning
confidence: 99%
“…This way of buying can be an opportunity to minimize risk of buying online. Trust and risk perception act as important factors to buy online (Liu and Forsythe, 2010;Azam and Qiang, 2012;Faqih, 2013). Information and communication technologies and virtual networks act as a platform for any necessary information for making a decision about a purchase.…”
Section: Introductionmentioning
confidence: 99%
“…This contributes some degree of risk or uncertainty to consumers regarding their purchase decision (Park & Kim, 2007;Azam, 2012).…”
Section: Online Shoppingmentioning
confidence: 99%